RESPONSE OF BREAD WHEAT YIELD AND COMPONENTS TO FOLIAR SILICON UNDER MOISTURE DEPLETION CONDITIONS - Khalid M. Deli; Makkiyah K. Alag (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Thi study aimed to assess the physiological effect of foliar silicon on the yield and its components of Bohouth 22cultivar bread wheat under conditions of moisture depletion. A field experiment was conducted at the Research Station E, College of Agricultural Engineering Sciences, University of Baghdad (Al-Jadriyah), during the 2022-2023 and 2023-2024 winter seasons. The nested design with three replicates was used to study three levels of moisture depletion (40%, 60%, and 80%) and four silicon concentrations (0, 150, 200, and 250 mg L-1).The results showed significant effects of depletion levels and silicon concentrations, with 40% and 60% depletion achieving the highest values ​​for the yield and its components. mean yields for the two seasons reached 5.627 and 4.792 t ha-1, and the highest water use efficiency for grain yield for the 60% depletion level compared to the 40% depletion factor reached 2.49 kg m3 of water in grains, and their water consumption reached 350.35 mm Season-1, which made 12.18% of water availability for the two seasons. The lowest values ​​were recorded at the depletion level of 80%.The silicon concentration of 200 mg L-1 also improved the yield and its components, as a mean for the two seasons. The grain yield reached 5.338 t h-1, and the water use efficiency of the grain yield amounted to 2.64 kg grains m-3 water compared to the control treatment sequentially. The interaction of the two study factors also had a significant effect on Most of the attributes.